Research on college students’ mental health education: the mediating role and the moderating effect of resource allocation - Li, Fawei; Yao, Hui (Frontiers in Psychology, 2026)
Amid global digital transformation and the expansion of higher education, college students are confronting increasingly salient mental health challenges stemming from academic pressure, career uncertainty, and social adaptation difficulties—rendering the development of a systematic mental health education system for college students an indispensable core strategy to mitigate the global college student mental health crisis. While existing research largely centers on fragmented intervention strategies or problem delineation, it lacks a systematic examination of the core components and intrinsic logic underlying a multi-level, multi-stakeholder collaborative support system. To address these research gaps, this study leverages multidimensional synergy theory to develop a tailored mental health education support system for college students, while clarifying the mediating role of educators’ mental health literacy and the moderating effect of mental health resource allocation. This system encompasses six core modules: educators’ mental health capacity building; dynamic monitoring of students’ psychological states; development of grassroots psychological service teams; tiered psychological crisis intervention; co-construction of mental health-conducive classroom environments; and targeted support for special student groups. Looking ahead, future research should transcend single-module effectiveness testing and shift toward cross-module, cross-level empirical validation of the mediating mechanism of educators’ mental health literacy and the moderating effect of mental health resource allocation within the system—thereby advancing a paradigm shift in the field from fragmented interventions to systematic science.